Analysis of Hospital Service Management from the Perspective of Local Balinese Wisdom - Sunariani, Ni Nyoman; Suidarma, I Made (Jurnal Economia, 2023)
This study aims to analyze the health service management of provincial hospitals (RSUDs) in Bali from the perspective of local wisdom, especially Tri Kaya Parisuda values and the integration of Tri Kaya Parisuda values with human capital theory (HCT). Structural equation modeling (SEM) was applied as the analysis technique in the study. The results showed that the management of health services at Bali's provincial hospitals was considered satisfactory and in accordance with the existing health service standards, although there were certain staff members who had not provided maximum service. Intellectual intelligence to think properly (manacika), communication equivalent to correct sayings (wacika),  and good employee behavior (kayika) contributed significant effects on the performance and service quality of RSUDs in Bali. This study discovered that the performance and quality of service were more dominantly affected by employee behavior than by intellectual intelligence or communication.